A dependência do petróleo e os riscos aos países emergentes : uma análise sobre a utilização dos fundos soberanos em momentos de crises econômicas - Bozz, Daniel (2023)
Amidst the countless problems caused by the coronavirus pandemic, which began in mid-2020, such as: movement of lockdowns, abrupt drop in levels of economic activity and uncertainty regarding the regrouping of conditions for the resumption of normality, the world experienced, once again, the downside caused by strong volatility in oil prices. After the first moments of the crisis, there was a reversal in scenario. Soon, commodities entered a strong appreciation cycle, which reflected in the countries' revenue. This magnitude’s movements are opportunities for economic advances for Brazil, which remains at the forefront of oil production. It depends, in part, on economists working in synergy with the State, to maintain and implement improvements in the framework of policies and strategies that offer minimum conditions for the existence of foundations for the growth of activity in the various phases of an economic cycle. The central objective of analyzing and comparing the advantages and disadvantages of using Sovereign Funds to stabilize oil prices as a tool to combat moments of volatility in emerging countries had chosen due to the importance that oil prices have on development of the country and the revenue generated from this sector. It is clear that new crises will occur in the future, and that the difficulty of pricing oil will remain high. However, the implementation of a plural tool, such as sovereign wealth funds, which allows raising resources – and directing them to contain damage in less auspicious moments – proves to be viable both for economies that seek to smooth the fluctuation in the prices of oil derivatives, and those that constantly try to expand their global operations through economic development. Therefore, the rearrangement of the global energy matrix opens space for dogmas to been overcome in favor of a transition that does not cause economic rifts for the agents involved. As long as they are structurally prepared.